Case Report: Various Abnormalities in Lipid and Glucose Metabolism Induced by Capecitabine - Anno, Takatoshi; Yamatsuji, Tomoki; Tomoda, Koichi; Nakanishi, Shuhei; Kaneto, Hideaki (Frontiers in Oncology, 2021)
Capecitabine has been used for the treatment of various types of tumors. The rare side effects induced by capecitabine have been reported as hypertriglyceridemia, acute pancreatitis associated with hypertriglyceridemia and hypertriglyceridemia complicated with hyperglycemia. The mechanisms of capecitabine-induced hypertriglyceridemia are unclear. In this report, we present a subject with sigmoid colon cancer and capecitabine-induced dyslipidemia. LDL-cholesterol level was markedly elevated throughout the long period of treatment with capecitabine. In addition, triglyceride level was high and not stable during the treatment period. Her dyslipidemia was ameliorated by the treatment with 5 mg of rosuvastatin, which is one of the HMG-CoA reductase inhibitors.